1986
DOI: 10.1002/jpln.19861490504
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on photosynthesis and assimilate translocation in Daucus carota L. as influenced by a varied phosphorus supply and changes in the endogenous hormonal system following GA3 treatments

Abstract: Investigations on phosphorous uptake, photosynthetic 14CO2 fixation, assimilate translocation and endogenous cytokinin concentrations were carried out with carrot plants at low and high level phosphorus supply. Source/sink relations were changed in favour of the source (shoot) and at the expence of the sink (root) by GA3 sprays. Following GA3 treatments the 2‐isopentenyl adenine (2iP) concentration in the tap root was strongly decreased. However, though sink development was drastically reduced due to this trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The results of yield dry matter and P content obtained in the present study are in good agreement with those of Bender et al (1986). The placement of phosphorus and potassium has increased the yield, phosphorus concentration in root in 1986, photosynthetic C0 2 fixation (yield, correlation between root and shoot dry weights) and assimilate translocation (dry matter content and correlation between dry matter and sucrose as well as total sugars).…”
Section: Organically Cultivated Carrotssupporting
confidence: 89%
“…The results of yield dry matter and P content obtained in the present study are in good agreement with those of Bender et al (1986). The placement of phosphorus and potassium has increased the yield, phosphorus concentration in root in 1986, photosynthetic C0 2 fixation (yield, correlation between root and shoot dry weights) and assimilate translocation (dry matter content and correlation between dry matter and sucrose as well as total sugars).…”
Section: Organically Cultivated Carrotssupporting
confidence: 89%
“…Because P is a component of RNA and DNA, as reported by Marschner (1995), it is reasonable to assume that the availability of P will have a significant impact on the biosynthesis of a variety of substances, including carbohydrates, proteins, and hormones. Additionally, Bender et al (1986) revealed that plants with an optimal P supply have much higher levels of photosynthetic CO 2 fixation and assimilate translocation than plants with low P levels.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Sobh et al, (2000) reported that, inoculation with phosphorus bio-fertilizers increased phosphatase activity, available P and producing growth regulating hormones. Moreover, Bender et al, (1986) revealed that, available P increased the photosynthetic Co2 fixation and assimilates translocation.…”
Section: Photosynthetic Pigmentsmentioning
confidence: 96%
“…Zayed (1998) proved that, phosphorus dissolving bacteria is known by its ability to dissolve the precipitation form phosphorus: Ca3 (PO4)2 depending on its ability to produce inorganic, organic acids and/or Co2. Bender et al, (1986) revealed that, phosphorus increased photosynthetic Co2 fixation and assimilates translocation in carrot plants. Rabinoveich et al, (1999) mentioned that, increased doses of bio-fertilizers for potato raised high concentration of denitrificating microorganisms.…”
Section: Carbohydrate Fractionsmentioning
confidence: 97%